1998
DOI: 10.1001/archotol.124.3.348
|View full text |Cite
|
Sign up to set email alerts
|

Selective Neck Dissection of Anatomically Appropriate Levels Is as Efficacious as Modified Radical Neck Dissection for Elective Treatment of the Clinically Negative Neck in Patients With Squamous Cell Carcinoma of the Upper Respiratory and Digestive Tracts

Abstract: Hypothesis:Patients with primary squamous cell carcinomas of the upper respiratory and digestive tracts with a greater than 20% probability of occult cervical metastases but with nodes clinically negative for metastatic disease warrant elective treatment of the neck for prognostic, diagnostic, and therapeutic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 23 publications
(40 reference statements)
0
68
0
1
Order By: Relevance
“…[18][19][20] Up to the late 1960s, RND remained the unquestioned standard surgical approach. Based on anatomic observations, a more conservative technique has been proposed.…”
Section: Commentmentioning
confidence: 99%
“…[18][19][20] Up to the late 1960s, RND remained the unquestioned standard surgical approach. Based on anatomic observations, a more conservative technique has been proposed.…”
Section: Commentmentioning
confidence: 99%
“…Clayman and Frank (1998) found that, despite clear guidelines, the anatomical boundaries in a SND are not as well defined as in a MRND, leading to increased rate of out-of-field recurrences. This outcome can also be affected by the operator's experience and judgement.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the anterolateral neck dissection groups these two previous surgical procedures together so that levels II, III, IV and VI are removed. It is important to emphasize the fact that the posterior border of dissection in all these selective procedures, except for the anterior dissection, is the cutaneous branches of the cervical plexus [18]; otherwise the risk of neck recurrences can be high [19,20]. Another aspect to be taken into consideration is the fact that although the spinal accessory nerve, the internal jugular vein, and the sternocleidomastoid muscle are preserved in the majority of these types of dissections, there is no reason why at least one of these three nonlymphatic structures cannot be sacrified [14].…”
Section: Neck Dissection Terminology and Classificationmentioning
confidence: 99%